Hubungan Keuangan Pemerintah Kabupaten dengan Pemerintah Nagari dalam Pelaksanaan Desentralisasi Fiskal di Kabupaten Tanahdatar - Roni Ekha Putera (JIANA ( Jurnal Ilmu Administrasi Negara ), 2009)
This research want to learn and describe about a couple thing related withfinancial format between kabupaten government and nagari government in implementingfiscal decentralization at Kabupaten Tanah Datar. The research question is how isfinancial format between kabupaten government and nagari government in implementingfiscal decentralization.To give explanation in research analysis, this research is a descriptive researchwith qualitative approach. Data collect by in-depth interview, observation, anddocumentation.In this research found that financial pattern or financial format between kabupatengovernment and nagari government obtain kabupaten government give simultan fund tonagari government every year with different amount in each nagari based on severalcriteria such as population, geographic vast, jorong amount, poor inhabitant amount andPBB reach. Fund come to nagari also have several type which is operational fund,empowering fund and development fund. For operational fund, there are arrangementsfrom kabupaten government so it can observe how the fund used, meanwhile fordevelopment fund it is not explicitly how much it amount but minimum is 100 millionsand maximum is 150 million. Development fund Liquefaction mechanism based onproposal submit by nagari government to kabupaten government via kecamatan. So,basically financial format build refer to PP No. 72 Year 2005 about Desa. So, in TanahDatar Kabupaten it does not know about DAUN / Nagari Allocate Fund but DAPN /Nagari Development Allocation Fund, in here possible to public participation in nagaridevelopment. Meanwhile the responsibilities notification for fund exertion report tokabupaten is via kecamatan.